Transnational religious actors and international order – the case of the Gülen Movement - Mirela Lončar (Chrześcijaństwo-Świat-Polityka)
This paper seeks to illustrate how religion can affect international relations and international order. Given that religion has been neglected as an important factor in political science, and then in theories of international relations, this paper will try to provide a modest contribution to the study of religion in the theory of international relations by analyzing the influence of transnational religious actors on the existing international order. The transnational religious actor analyzed in this paper is the Gülen Movement – Hizmet Movement. Hizmet Movement is a transnational Islamic movement formed in the Republic of Turkey in the 1960s by the former Turkish Imam Muhammad Fethullah Gülen. Today, this Islamic movement has many institutions, organizations and members around the world. The Gülen Movement aims to create a transnational society - the Golden Generation of Ideal People (Altın Nesıl), and thus represents a challenge for the existing international order.